Adapt and strive: How ventures under resource constraints create value through business model adaptations. (September 2017) - Dopfer, Martina; Fallahi, Sara; Kirchberger, Markus; Gassmann, Oliver
Abstract : This paper looks into how new ventures organize their business models in order to meet their available resources. It employs the business model as the unit of analysis to investigate the role and nature of business model adaptation as a coping mechanism with resource constraints. By drawing on a case study with two ventures starting with different resources, the paper shows how those ventures use business model adaptation under resource constraints as a way to create comparable offerings. Business model adaptation involves a process of continuous search, selection, and improvement in value creation, value proposition, and value capture, based on the surrounding environment. For the two new ventures included in this study, early business model adaptations were related to (1) market — geography and customer, (2) strategy — marketing, sales, and growth, (3) profit — profit formula and cost structure, and (4) structures, processes, and capabilities. This paper also shows how the adaptation process is conditioned by the venture's stock and flow of resources. Bringing a resource perspective into the process of business model adaptation implies practical implications for new ventures that are developing and adapting their business models to strategically co‐develop their offering with their resources such that they match required adaptations.